Reflection of Undergraduate Students on Translation Process: An Outlook of Translation Teaching in University - Roswani Siregar; Risnawaty Risnawaty; Yulia Arfanti; Milisi Sembiring (Bina Nusantara University, 2020)
The research attempted to recognize students’ comprehension in adopting a set of procedures in the translation process compared to the translation-professional choices in real-situation. Thus, two sets of questionnaires were provided for students and professional translators. The qualitative method was employed in conducting the research. The first questionnaire enabled students to express their feelings, thoughts, and ideas concerning the translation course and process. This reflection revealed the students’ strategies, interests, and motivation in attending the course. It also allowed the student to see the importance and benefit of the course. On the other hand, the second questionnaire drew some insight into professional translators’ choice in doing a translation, particularly on strategy in dealing with texts. Those finding provides an opportunity for teachers to identify the students’ needs in learning and practicing the translation as close as the professional does and finally to find the best approach in teaching translation.